Eventonym: A Specific Type of Advertising Proper Name - Tatyana P. Romanova (Вопросы ономастики, 2020)
The paper uses a structural-semiotic approach to analyse the advertising names of special events (festivals, marathons, competitions, exhibitions, fairs, and other campaigns and projects for mass appeal) held mainly in the Samara region. Such targeted events, differing in their format, status, topic, frequency, setting, and parameters of the target audience, cut across all spheres of modern Russian society. The paper deals with eventonyms, i.e. advertising proper names of various socio-cultural activities aimed at promoting an event. According to the research hypothesis, eventonyms are characteristically associated with the language of advertising and marketing discourse. Most event names include semantic components having a deliberate pragmatic effect on the addressee. They also perform an advertising function due to informative, attractive, and suggestive components, expressiveness, and emotional coloring. Using them as part of a creolized text maximizes the pragmatic impact of eventonyms through a combination of verbal and non-verbal constituents. The study specifies the status of eventonyms in the field of onomastics; analyses the communicative potential of the two main naming patterns (descriptive and symbolic); explores the pragmatic and suggestive potential of eventonyms and their typological characteristics. Apart from various advertising contexts, eventonyms are also used as keywords in media texts, having a direct impact on the success of a promotional campaign and communicative efficiency of the message. The properties of event names in advertising and information spheres are a priority object of modern linguistic pragmatics. Researching the communicative capacity of eventonyms is most relevant today due to the need for better utilization of this new soft power tool in order to manage its effect on target audiences.